Learning Management Of Students' English Speaking AbilityAt 01 State Junior High School of Ungaran - Ekaningsih, Nur; , Prof. Dr. Sutama, M.Pd; , Dr. Phil. Dewi Candraningrum, M.Ed (2013)
The objectives of the research are consisting of three descriptions. Firstly, it is describing as a whole the learning management of English teaching. Secondly, it is to describe in detail about the learning management of Students' English speaking ability. At last to describe Evaluation of Students' English speaking ability. It is descriptive qualitative research and ethnography design which describes the learning management of Students' English Speaking Ability. The data are in the forms of information consisting of systematic thought, sentences, and experience based on specific context. The data sources are event, document, informant, and artifact. Techniques used in data collection are in-depth interview, documentation and observation. Data analysis of this research is interactive analysis which includes reducing data, data categorization, synthesis, and hypothesis. Data validity of this research is the validity test to find the level of consideration uses triangulation, extended observation, friends' discussion, negative case analysis and reference materials. The research results show that the learning management of English teaching by expanding time and integrated basic skills in combining national and international curriculum structure will make students learn broaden materials and have longer time to express ideas for communicating. The learning management of English teaching by inserting more expressions and students' custom in syllabus and lesson plan will create good learning partnership between teachers and students. The learning management of students' English speaking ability by enhancing students' opportunities to produce the language in interesting and experience activities like in a real world theme will make students familiar and enthusiastic to speak English. The evaluation of students' English speaking ability on sociolinguistic competence by interview, in pairs dialogue and individual speech will be useful for students to encourage and facilitate themselves on English speaking. As an advice, the Principal should manage extra times in preparing English teaching and support teachers with technological aids. Teachers should innovate themselves in the English teaching as integrated skills and evaluate students' speaking ability continuously in the area of grammatical and strategic competence. Supporting experienced activities for students' in English to the real English learning should be varieties. Finally, these will make students' practically pronounce English as their habit to make them perfect.